La libertad de expresión como derecho constitucional y su incidencia en el honor de las personas - Assen Troncoso, Angélica Mariela (2015)
This legal research project entitled "Freedom of expression as a constitutional right and its impact on the honor of the people", focuses on a civil matter and also on Human Rights. The protection of honor and dignity is the conditioning of the government to defend the actions against journalists and justify restrictive and undemocratic as the Communications Law bill. The government cites Article 11 of the American Convention on Human Rights to restrict the right, while the journalists and people do not believe in that. Public officials should be more tolerant to criticism and accept expressions, even shocking or cuestionadoras because they are characters that manage public goods, the debate made to the questions that have been made to the press, the arguments as justification to limit freedom expression, have not had enough resonates with people. Honor and dignity are indeed a fundamental human right to the same status as freedom of expression. But honor is a very personal, individual right. Meanwhile, freedom of expression is an individual right and collective at the same time. To the extent that it has repeatedly stated that without freedom of expression there can be no full democracy.